"Driven and Tense, Stressed Out and Anxious": Clinicians' Perceptions of Post-Traumatic Stress Disorder Symptom Expressions in Adults with Autism and Intellectual Disability. Issue 3 (2nd July 2020) - Kildahl, Arvid Nikolai; Helverschou, Sissel Berge; Bakken, Trine Lise; Oddli, Hanne Weie
ABSTRACT: Introduction: Individuals with autism spectrum disorder (ASD) and intellectual disability (ID) seem to be at increased risk for post-traumatic stress disorder (PTSD), but knowledge is sparse regarding its identification in this population. Previous research indicates that certain symptoms of PTSD may be more easily recognized, and that identifying reexperiencing and avoidance is particularly challenging. Methods: Interpretative phenomenological analysis was used to explore 18 experienced clinicians' perceptions of PTSD symptom expression in ASD and ID through individual, qualitative interviews. Results: Informants provided examples from all symptom groups, but these differed in how frequently they were described. Recognition of reexperiencing may rely on knowledge about individuals' trauma experience. Avoidance may present in a wider range of ways. Conclusion: Development of reexperiencing and avoidance may follow different trajectories in this population, contributing to challenges in recognition. Reexperiencing may be more severe in ASD/ID. Implications are discussed in light of current diagnostic criteria.